2019
DOI: 10.12998/wjcc.v7.i17.2438
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, clinical features, and short-term prognosis of spontaneous fungal peritonitis in cirrhosis: A matched case-control study

Abstract: BACKGROUNDSpontaneous peritonitis is one of the most common infectious complications in cirrhotic patients with ascites. Spontaneous fungal peritonitis (SFP) is a type of spontaneous peritonitis that is a less recognized but devastating complication in end-stage cirrhosis. Although high mortality was previously noted, scant data are available to fully define the factors responsible for the occurrence of SFP and its mortality.AIMTo illustrate the differences between SFP and spontaneous bacterial peritonitis (SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Early identification and diagnosis of cirrhotic patients with SFP/fungiascites is a critical strategy to improve the clinical prognosis of these patients. Although Huang C's study analyzed risk factors for the development of SFP, there is no further information on how to differentiate SFP [24]. It was reported that higher MELD scores or Child-Pugh scores were associated with the development of SFP [13,25].…”
Section: Discussionmentioning
confidence: 99%
“…Early identification and diagnosis of cirrhotic patients with SFP/fungiascites is a critical strategy to improve the clinical prognosis of these patients. Although Huang C's study analyzed risk factors for the development of SFP, there is no further information on how to differentiate SFP [24]. It was reported that higher MELD scores or Child-Pugh scores were associated with the development of SFP [13,25].…”
Section: Discussionmentioning
confidence: 99%